Asymmetry between recipients and donors as a health problem. Investigation of family acceptance or refusal to donate organs and tissues - Augsburger, Ana Cecilia (2021)
The objective of the research was to investigate the knowledge, attitudes, and beliefs of family groups involved in decision-making processes about the procurement and donation of organs. A qualitative study was carried out with a descriptive and interpretive design. Fourteen potential donor family groups participated in the study who accepted or opposed the organ donation process. A thematic script was created for the development of interviews with 10 families who accepted and 4 who rejected the donation. The results showed that decisions were made easier when the family had information about the donor's wishes. Those who opposed were unaware of the will and did not have precise communication with potential givers on the matter. Within the family group, mothers assumed a relevant role at the time of the favorable definition. The act of donation carries a positive vision of generosity and altruism, although prejudices and mistrust remains regarding the procedures and transparency of the professionals and institutions that participate. The interviewees had difficulty determining the identity of the person who requested the donation, with marked ignorance of the institutions and norms that regulate this action. The importance of strengthening communication in the population about the importance of organ donation, as well as transparency and institutional trust, is concluded. Dialogue within the family about people's willingness to donate is relevant for making a favorable decision.